The experiences of parents where pregnancy ended in an unplanned caesarean section - C. C. Ceronio; C. S. Dörfling; A. G. W. Nolte (AOSIS, 1995)
The purpose of this study to determine the experiences of parents prior to, during and following an unplanned caesarean section. Parents who experienced this event had mixed emotions. The related occurrences may have influenced their behaviour and consequently their relationships with their spouses, themselves and their environment. These continually interacted with each other and thus needed to be looked at in context. 'The Nursing of the Whole Person Theory' ensured a holistic approach to the parents. Unstructured, in-depth interviews held with five mothers and five fathers, respectively, on day three post-delivery, were transcribed and analysed. At six weeks a follow-up semi-structured questionnaire was answered by these same respondents and analysed The experiences of the parents were then compared,